Applying attitude theory to determine user security approaches - Szűcs, Kata Rebeka; Tick, Andrea; Reicher, Regina Zsuzsanna (Serbian Journal of Management, 2024)
Mobile phones and internet form a crucial part of modern life, which raises important questions, such as security, data protection and privacy. Countless studies examine what influences users’ approaches towards security. The attitude theory gives the basic background to the present study through which the topics of cyber safety and security, data protection and privacy are examined. The three components of attitude, which served as the three pillars of the applied survey, are: (1) the cognitive component (belief and knowledge), (2) the affective component (feelings) and (3) the behavioural component (the effect of the attitude on the users’ behaviour). Self-reported security knowledge and feelings about security were assessed, out of which three factors were formed using EFA. The security behaviour of each factor was examined to determine the consistency of the responses. Moreover, the three factors helped to identify three separate clusters. As a conclusion it can be stated that the theory of attitudes can help understanding user security behaviour better. Finally, future research directions are suggested.